Synthesis and bioactivity of erythro-nordihydroguaiaretic acid, threo-(–)-saururenin and their analogues - Supplementary Material - YAMU XIA, YUANYUAN ZHANG, WEI WANG, YINING DING and RUI HE (Journal of the Serbian Chemical Society, 2010)
n/a